Positive electrode for alkaline battery, alkaline battery and method for producing same
By incorporating tellurium in the silver oxide-based positive electrode and alkaline electrolyte, the alkaline battery achieves improved charge/discharge cycle characteristics and reduced internal resistance, addressing the limitations of cadmium-containing alkaline batteries.
Patent Information
- Application Number
- JP2021561396
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-30
- Filing Date
- 2020-11-24
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-11-24
AI Technical Summary
Alkaline batteries using silver oxide as a positive electrode active material face challenges in improving charge and discharge cycle characteristics and reducing internal resistance, while avoiding the environmental impact of cadmium components.
The positive electrode contains silver oxide with a minimum 0.4 parts by mass of tellurium or its compound per 100 parts by mass of silver, excluding cadmium, and is assembled with an alkaline electrolyte containing tellurium or its compound, enhancing the electrode's performance.
This configuration improves charge/discharge cycle characteristics and reduces internal resistance in alkaline batteries, ensuring efficient operation without cadmium's environmental impact.
Smart Images

Figure 0007611850000004 
Figure 0007611850000005 
Figure 0007611850000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode that uses silver oxide as a positive electrode active material and is applicable to an alkaline battery, and to an alkaline battery and a method for producing the same. [Background technology]
[0002] Alkaline batteries that use silver oxide as a positive electrode active material and an alkaline electrolyte are widely used as primary batteries, while the use of alkaline batteries having such a configuration as secondary batteries is also being considered.
[0003] Various improvements have been made to such alkaline batteries. For example, Patent Document 1 discloses that silver peroxide for batteries [silver (II) oxide, AgO], which has low stability in potassium hydroxide electrolyte and generates oxygen, can be prevented from generating oxygen by adding a predetermined amount of cadmium and tellurium components. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 57-11823 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the use of cadmium places a large burden on the environment, and the structure described in Patent Document 1 cannot be directly applied to alkaline batteries. On the other hand, for alkaline batteries using silver oxide as the positive electrode active material, further improvements in the characteristics are required for both primary and secondary batteries, and research into this issue is ongoing.
[0006] The present invention has been made in view of the above circumstances, and a first object of the present invention is to provide a positive electrode for an alkaline battery that can improve charge-discharge cycle characteristics, an alkaline battery having excellent charge-discharge cycle characteristics, and a method for producing the same.
[0007] A second object of the present invention is to provide a positive electrode for an alkaline battery capable of reducing the internal resistance, an alkaline battery having reduced internal resistance, and a method for producing the same. [Means for solving the problem]
[0008] The positive electrode for an alkaline battery of the present invention contains silver oxide as a positive electrode active material, and also contains tellurium or a compound thereof, the content of elemental tellurium in the positive electrode being 0.4 parts by mass or more relative to 100 parts by mass of the total amount of elemental silver in the positive electrode active material, and is substantially free of cadmium.
[0009] In addition, the alkaline battery of the present invention has a positive electrode containing silver oxide as a positive electrode active material, a negative electrode, a separator, and an alkaline electrolyte as power generating elements, at least one of which contains tellurium or a compound thereof, the total content of elemental tellurium contained in the contents of the battery is 0.4 parts by mass or more when the total amount of elemental silver in the positive electrode active material is 100 parts by mass, and the positive electrode is substantially free of cadmium.
[0010] Furthermore, the method for producing an alkaline battery of the present invention is characterized in that the positive electrode for an alkaline battery of the present invention is used as the positive electrode.
[0011] In another aspect of the method for producing an alkaline battery of the present invention, the alkaline electrolyte is an alkaline electrolyte in which tellurium or a compound thereof is dissolved. Effect of the Invention
[0012] According to one aspect of the present invention, it is possible to improve the charge-discharge cycle characteristics of an alkaline battery, and according to another aspect of the present invention, it is possible to reduce the internal resistance of an alkaline battery. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view illustrating an example of an alkaline battery of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view illustrating a schematic diagram of another example of an alkaline battery of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The positive electrode for an alkaline battery of the present invention (hereinafter sometimes simply referred to as the "positive electrode") contains silver oxide as a positive electrode active material, and further contains tellurium (Te) or a compound thereof, the content of elemental tellurium in the positive electrode being 0.4 parts by mass or more relative to 100 parts by mass of the total amount of elemental silver in the positive electrode active material, and is substantially free of cadmium.
[0015] As shown in Patent Document 1, when TeO2 is added alone to silver oxide (II), the amount of oxygen generated in the potassium hydroxide electrolyte is greater than when silver oxide (II) is added alone (Table 1, page 3, Test Nos. 1-2). Therefore, Patent Document 1 avoids the above problem by adding a combination of a specified amount of cadmium component and a specified amount of tellurium component.
[0016] However, according to the investigations of the present inventors, it has been found that by incorporating a predetermined amount of tellurium or a compound thereof into at least one of the power generating elements, i.e., the positive electrode, the negative electrode, the separator, and the alkaline electrolyte, particularly into the positive electrode, it is possible to reduce the internal resistance of the battery or improve the charge / discharge cycle characteristics, even without incorporating cadmium (Cd) into the positive electrode.
[0017] In addition, it was found that when silver oxide (I) is contained as the positive electrode active material, particularly when the proportion of silver oxide (I) in the silver oxide is high, the problem of oxygen generation as shown in Patent Document 1 does not become apparent.
[0018] Tellurium or its compound may be contained in, for example, any one of the power generating elements. However, when tellurium or its compound is contained in the negative electrode or separator, it is presumed that these additives first dissolve in the alkaline electrolyte and migrate to the positive electrode, and then act on silver oxide, which is the positive electrode active material, to reduce the internal resistance of the battery or, in the case of a secondary battery, improve the charge-discharge cycle characteristics.
[0019] Therefore, it is preferable to dissolve tellurium or a compound thereof in an alkaline electrolyte in advance and assemble an alkaline battery using the prepared alkaline electrolyte.
[0020] Furthermore, by incorporating tellurium or a compound thereof in the positive electrode, these additives dissolve in the alkaline electrolyte and then act directly in the positive electrode, allowing the additives to efficiently exert their functions, which is more preferable.
[0021] The content of tellurium or its compound may be adjusted so that the total content of elemental tellurium contained in the contents in the battery is 0.4 parts by mass or more when the total amount of elemental silver in the positive electrode active material is 100 parts by mass. When the contents are only a power generating element, the content of tellurium or its compound may be adjusted so that the total content of elemental tellurium held by each component of the power generating element is within the above range. In other words, the total amount of elemental tellurium dissolved and held in the electrolyte and elemental tellurium contained in the tellurium or its compound held in a state in contact with the electrolyte and capable of dissolving in the electrolyte may be within the above range.
[0022] Specific examples of the additives contained in the power generating element include tellurium (metallic tellurium); tellurium oxides such as tellurium dioxide and tellurium trioxide; telluric acid or its salts (lithium salt, sodium salt, etc.); tellurous acid or its salts (sodium salt, potassium salt, barium salt, etc.); and the like.
[0023] The configuration of the present invention will be described in detail below.
[0024] <Positive electrodes for alkaline batteries> Examples of positive electrodes for alkaline batteries include a molded body of a positive electrode mixture containing a positive electrode active material and a conductive assistant, and a structure in which a layer of a positive electrode mixture containing a positive electrode active material and a conductive assistant (positive electrode mixture layer) is formed on one or both sides of a current collector.
[0025] Silver oxide, which is a positive electrode active material, may be a composite oxide, such as silver oxide (I) such as Ag2O or silver oxide (II) such as AgO. It may also be a mixture of silver oxide (I) and other silver oxides such as silver oxide (II). However, in order to increase the stability of the positive electrode active material, the proportion of silver oxide (I) in the total amount of silver oxide contained in the positive electrode (in the total amount of silver oxide in the positive electrode mixture) is preferably 60% by mass or more, more preferably 85% by mass or more. Since the silver oxide may be entirely silver oxide (I), the upper limit of the proportion of silver oxide (I) in the total amount of silver oxide contained in the positive electrode (in the total amount of silver oxide in the positive electrode mixture) is 100% by mass.
[0026] In the present invention, it is not necessary to include cadmium in the positive electrode, and a positive electrode that does not substantially contain cadmium can be constructed. Here, "substantially does not contain cadmium" means that the content of cadmium (Cd) is 0.1 parts by mass or less when the total amount of silver element in the positive electrode active material is 100 parts by mass, but from the viewpoint of environmental load, it is preferable to use a positive electrode active material that does not contain cadmium at all or contains cadmium at a content equivalent to that of an impurity.
[0027] The particle size of the silver oxide is not particularly limited, but the average particle size is preferably 10 μm or less, and more preferably 2 μm or less. When silver oxide of such a size is used, the utilization rate during charging is improved, especially when the positive electrode is applied to a secondary battery.
[0028] However, since silver oxide with too small a particle size is difficult to produce and handle thereafter, the average particle size of the silver oxide is preferably 0.01 μm or more, and more preferably 0.03 μm or more.
[0029] The average particle size of silver oxide and each particle (silver oxide, insulating inorganic particles, graphite, etc.) described later in this specification is determined by dispersing these particles in a medium that does not dissolve the particles using a laser scattering particle size distribution analyzer (e.g., "LA-920" manufactured by Horiba, Ltd.), and measuring the particle size at a cumulative frequency of 50% on a volume basis (D 50 ).
[0030] When the positive electrode mixture contains tellurium or a compound thereof, the content of the additive is adjusted to 0.4 parts by mass or more, more preferably 1 part by mass or more, and particularly preferably 2 parts by mass or more, per 100 parts by mass of the total amount of silver (Ag) element in silver oxide, which is the positive electrode active material, in order to better ensure the above-mentioned effects due to its use. However, if the amount of the additive in the positive electrode mixture is too large, the amount of silver oxide, which is the active material, may decrease, resulting in a decrease in the capacity of the battery or a decrease in the load characteristics. Therefore, the content of the additive in the positive electrode mixture is adjusted to 10 parts by mass or less, more preferably 5 parts by mass or less, and particularly preferably 4 parts by mass or less, per 100 parts by mass of the total amount of silver (Ag) element in silver oxide.
[0031] Examples of the conductive assistant in the positive electrode mixture layer include carbonaceous materials such as carbon black and graphite. It is more preferable to use carbon black and graphite in combination as the conductive assistant.
[0032] The use of carbon black makes it easy to form a good conductive network in the positive electrode mixture compact and in the positive electrode mixture layer. This increases the number of contact points with silver oxide, which is the positive electrode active material, compared with, for example, the use of graphite alone, and makes it possible to further reduce the electrical resistance within the positive electrode mixture compact and in the positive electrode mixture layer, thereby making it possible to further improve the reaction efficiency of the positive electrode active material.
[0033] On the other hand, when carbon black is used alone, it may be necessary to use a binder to improve the moldability depending on the thickness of the positive electrode mixture compact or positive electrode mixture layer. However, when graphite is also used in combination, the moldability of the positive electrode mixture is improved. Therefore, even when the positive electrode mixture compact or positive electrode mixture layer is thin, for example, 0.4 mm or less, and more preferably 0.3 mm or less, the moldability is good, and it becomes easy to prevent production defects even without using a binder.
[0034] The graphite in the positive electrode mixture may be either natural graphite (such as flake graphite) or artificial graphite, and one or more of these may be used.
[0035] As described above, graphite has the function of improving the formability of the positive electrode mixture compact and the positive electrode mixture layer. From the viewpoint of better exerting this function, the graphite preferably has an average particle size of 1 μm or more, and more preferably 2 μm or more, and from the viewpoint of improving electrical conductivity, the average particle size is preferably 7 μm or less, and more preferably 5 μm or less.
[0036] Examples of carbon black for the positive electrode mixture include furnace black, channel black, acetylene black, thermal black, etc., and one or more of these can be used. Among these carbon blacks, acetylene black, which has high conductivity and low impurity content, is preferably used.
[0037] In addition, it is preferable that the positive electrode mixture further contains insulating inorganic particles, which can further improve the charge / discharge cycle characteristics, particularly in the case of a secondary battery. In addition, when the insulating inorganic particles are used, the positive electrode mixture can further contain carbon black and graphite, which can further improve the charge / discharge cycle characteristics in the case of a secondary battery.
[0038] The insulating inorganic particles for the positive electrode mixture include particles of an oxide of at least one element selected from Si, Zr, Ti, Al, Mg, and Ca. Specific examples of the oxide include Al2O3, TiO2, SiO2, ZrO2, MgO, CaO, AlOOH, and Al(OH)3, and particles that are insoluble or poorly soluble in an alkaline electrolyte are preferably used. These insulating inorganic particles may be used alone or in combination of two or more kinds.
[0039] If the particle size of the insulating inorganic particles is too large, there is a risk that the effect of improving the charge-discharge cycle characteristics may be reduced in the case of, for example, a secondary battery, and therefore the average particle size of the insulating inorganic particles is preferably 0.5 μm or less, and more preferably 0.3 μm or less.
[0040] Furthermore, if the particle size of the insulating inorganic particles is too small, there is a risk of a decrease in charging efficiency (initial capacity) in the case of, for example, a secondary battery, etc. Therefore, the average particle size of the insulating inorganic particles is preferably 0.01 μm or more, and more preferably 0.05 μm or more.
[0041] As for the composition of the positive electrode mixture, in order to ensure capacity, the content of silver oxide, which is the positive electrode active material, is, for example, preferably 60 mass % or more, more preferably 80 mass % or more, and particularly preferably 90 mass % or more.
[0042] Furthermore, the content of the conductive assistant in the positive electrode mixture is preferably 0.2 mass % or more from the viewpoint of conductivity, preferably 0.5 mass % or more, and particularly preferably 1 mass % or more, while in order to prevent a decrease in capacity and gas generation during charging (in the case of a secondary battery), the content is preferably 8 mass % or less, more preferably 7 mass % or less, even more preferably 5 mass % or less, and particularly preferably 3 mass % or less.
[0043] When carbon black and graphite are contained in the positive electrode mixture, the graphite content is preferably 1% by mass or more, and more preferably 2% by mass or more, from the viewpoint of ensuring the above-mentioned effects of combined use with carbon black. When carbon black and graphite are contained in the positive electrode mixture, the graphite content is preferably 7% by mass or less, and more preferably 4% by mass or less, from the viewpoint of preventing a decrease in the capacity of the battery due to an excessive decrease in the amount of silver oxide in the positive electrode mixture.
[0044] In addition, when carbon black and graphite are contained in the positive electrode mixture, the carbon black content is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, from the viewpoint of ensuring the above-mentioned effect by using it in combination with graphite. However, if the amount of carbon black in the positive electrode mixture is too large, for example, when the battery is stored at high temperature, there is a risk that the amount of swelling of the positive electrode will increase. Therefore, from the viewpoint of suppressing the swelling of the positive electrode during storage of the battery (especially storage at high temperature of about 60° C.) and improving the storage characteristics of the battery, the carbon black content in the positive electrode mixture containing carbon black and graphite is preferably 1.5% by mass or less, more preferably 1% by mass or less.
[0045] In addition, when insulating inorganic particles are contained in the positive electrode mixture, the content is preferably 0.1% by mass or more, more preferably 3% by mass or more, from the viewpoint of ensuring the effect of its use (especially the effect of improving the charge-discharge cycle characteristics in the case of a secondary battery). However, if the amount of insulating inorganic particles in the positive electrode mixture is too large, the filling amount of the positive electrode active material decreases, leading to a decrease in the capacity of the battery, and depending on the type of insulating inorganic particles, there is also a risk that the discharge capacity of a secondary battery may suddenly decrease as the charge-discharge cycle progresses. Therefore, the content of insulating inorganic particles in the positive electrode mixture is preferably 7% by mass or less, more preferably 5% by mass or less.
[0046] As described above, the positive electrode mixture compact and the positive electrode mixture layer can be formed without using a binder, but when it is necessary to increase the strength (when graphite is not used as a conductive assistant, etc.), a binder may be used. Examples of binders for the positive electrode mixture include fluororesins such as polytetrafluoroethylene (PTFE). When a binder is used, the content of the binder in the positive electrode mixture is preferably 0.1 to 20 mass%.
[0047] In the case of a molded body of a positive electrode mixture, the positive electrode can be produced by, for example, pressurizing a positive electrode mixture prepared by mixing silver oxide, tellurium or a compound thereof, which are positive electrode active materials, and a conductive assistant, and, if necessary, an alkaline electrolyte (the same as the alkaline electrolyte injected into a battery can be used), into a predetermined shape.
[0048] Furthermore, in the case of a positive electrode having a positive electrode mixture layer and a current collector, for example, a positive electrode active material such as silver oxide, tellurium or a compound thereof, and a conductive assistant are dispersed in water or an organic solvent such as N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode mixture-containing composition (slurry, paste, etc.), which is then applied onto a current collector, dried, and, if necessary, subjected to a pressing process such as a calendaring process, thereby producing the positive electrode.
[0049] However, the positive electrode is not limited to those produced by the above-mentioned methods, and may be produced by other methods.
[0050] When the positive electrode mixture molded body is used as the positive electrode, the thickness is preferably 0.15 to 4 mm. On the other hand, when the positive electrode has a positive electrode mixture layer and a current collector, the thickness of the positive electrode mixture layer (thickness per one side of the current collector) is preferably 30 to 300 μm.
[0051] When a current collector is used for the positive electrode, examples of the current collector include those made of stainless steel such as SUS316, SUS430, and SUS444; aluminum or aluminum alloy; and examples of the form of the current collector include plain woven wire mesh, expanded metal, lath mesh, punching metal, metal foam, and foil (plate). The thickness of the current collector is preferably, for example, 0.05 to 0.2 mm. It is also desirable to apply a paste-like conductive material such as carbon paste or silver paste to the surface of such a current collector.
[0052] <Alkaline batteries> The alkaline battery of the present invention has, as power generating elements, a positive electrode containing silver oxide as a positive electrode active material, a negative electrode, a separator, and an alkaline electrolyte. The alkaline battery of the present invention includes primary batteries and secondary batteries.
[0053] Here, the positive electrode can be the positive electrode for an alkaline battery of the present invention.
[0054] For the negative electrode of an alkaline battery, for example, zinc particles, i.e., particles or zinc foil made of pure zinc (including unavoidable impurities) or zinc alloy, are used as an active material. Examples of alloy components of zinc alloy particles include indium, bismuth, aluminum, etc. (the balance being zinc and unavoidable impurities). The zinc particles in the negative electrode may be made of only one type of particles with a single composition, or may contain two or more types of particles with different compositions.
[0055] However, it is preferable to use zinc particles that do not contain mercury as an alloy component. If such zinc particles are used in a battery, environmental pollution caused by the disposal of the battery can be suppressed. Also, for the same reason as in the case of mercury, it is preferable to use zinc particles that do not contain lead as an alloy component.
[0056] Regarding the particle size of the zinc particles, for example, the ratio of particles having a particle size of 75 μm or less in the total powder is preferably 50 mass% or less, more preferably 30 mass% or less, and the ratio of particles having a particle size of 100 to 200 μm is 50 mass% or more, more preferably 90 mass% or more. The particle size of the zinc particles referred to here is a value obtained by the same measurement method as the average particle size measurement method of the silver oxide described above.
[0057] The negative electrode may contain, for example, a gelling agent (sodium polyacrylate, carboxymethyl cellulose, etc.) added as necessary in addition to the zinc particles, and may use a negative electrode agent (gelled negative electrode) formed by adding an alkaline electrolyte to the above. The amount of the gelling agent in the negative electrode is preferably, for example, 0.5 to 1.5 mass %.
[0058] The negative electrode can also be a non-gelled negative electrode that does not substantially contain a gelling agent as described above (note that in the case of a non-gelled negative electrode, a gelling agent may be contained as long as the alkaline electrolyte present in the vicinity of the zinc particles is not thickened, so "substantially not containing a gelling agent" means that the gelling agent may be contained to an extent that does not affect the viscosity of the alkaline electrolyte). In the case of a gelled negative electrode, an alkaline electrolyte is present in the vicinity of the zinc particles together with a gelling agent, but the alkaline electrolyte is thickened by the action of the gelling agent, and the movement of the alkaline electrolyte and therefore the movement of ions in the electrolyte are suppressed. For this reason, the reaction rate at the negative electrode is suppressed, which is considered to hinder the improvement of the load characteristics (particularly the heavy load characteristics) of the battery. In contrast, by making the negative electrode non-gelled and maintaining a high movement rate of ions in the alkaline electrolyte without increasing the viscosity of the alkaline electrolyte present in the vicinity of the zinc particles, the reaction rate at the negative electrode can be increased, and the load characteristics (particularly the heavy load characteristics) can be further improved.
[0059] The alkaline electrolyte contained in the negative electrode can be the same as that injected into the battery.
[0060] The content of zinc particles in the negative electrode is, for example, preferably 60% by mass or more, more preferably 65% by mass or more, and is preferably 75% by mass or less, more preferably 70% by mass or less.
[0061] The negative electrode preferably contains an indium compound, which makes it possible to more effectively prevent gas generation due to the corrosion reaction between zinc particles and the alkaline electrolyte.
[0062] Examples of the indium compound include indium oxide and indium hydroxide.
[0063] The amount of the indium compound used in the negative electrode is preferably 0.003 to 1 per 100 zinc particles in terms of mass ratio.
[0064] When the negative electrode contains tellurium or a compound thereof, the content is adjusted to 0.4 parts by mass or more, more preferably 1 part by mass or more, and particularly preferably 2 parts by mass or more, per 100 parts by mass of the total amount of silver (Ag) element in the silver oxide, which is the positive electrode active material, in order to better ensure the above-mentioned effects due to its use. However, if the amount of the additive in the negative electrode is too large, the amount of zinc particles or zinc foil, which is the negative electrode active material, may decrease, resulting in a decrease in the capacity of the battery or a decrease in the load characteristics. Therefore, the content of the additive in the negative electrode is adjusted to 10 parts by mass or less, more preferably 5 parts by mass or less, and particularly preferably 4 parts by mass or less, per 100 parts by mass of the total amount of silver (Ag) element in the silver oxide.
[0065] The alkaline electrolyte used in the alkaline battery is preferably an aqueous solution of one or more types of alkali metal hydroxide (sodium hydroxide, potassium hydroxide, lithium hydroxide, etc.), and potassium hydroxide is particularly preferred. For example, in the case of an aqueous solution of potassium hydroxide, the concentration of potassium hydroxide is preferably 20% by mass or more, more preferably 30% by mass or more, and preferably 40% by mass or less, more preferably 38% by mass or less. By adjusting the concentration of the aqueous solution of potassium hydroxide to such a value, an alkaline electrolyte with excellent conductivity can be obtained.
[0066] When dissolving tellurium or a compound thereof in an alkaline electrolyte, the content of the additive is preferably adjusted so that the amount of tellurium (Te) element is 0.4 parts by mass or more relative to 100 parts by mass of the total amount of silver (Ag) element in silver oxide, which is the positive electrode active material. For example, in order to facilitate the above adjustment, the content of the additive in the electrolyte is preferably adjusted so that the content of tellurium (Te) element is 0.1% by mass or more, more preferably 1% by mass or more, and particularly preferably 2% by mass or more. If the content of the additive in the alkaline electrolyte becomes too large, the viscosity of the electrolyte may increase and the ion conductivity may decrease, which may result in a decrease in the load characteristics of the battery. Therefore, the content of the additive in the alkaline electrolyte is preferably adjusted so that the content of tellurium (Te) element is 10% by mass or less, more preferably 8% by mass or less, and particularly preferably 6% by mass or less.
[0067] In addition to the above-mentioned components, various known additives may be added to the alkaline electrolyte as necessary within the range that does not impair the effects of the present invention. For example, zinc oxide may be added to prevent corrosion (oxidation) of zinc particles used in the negative electrode of the alkaline battery. Zinc oxide may also be added to the negative electrode.
[0068] When the alkaline battery is a secondary battery, the alkaline electrolyte may contain one or more compounds selected from the group consisting of manganese compounds, tin compounds, and indium compounds dissolved therein.
[0069] When an alkaline secondary battery having a positive electrode containing silver oxide as a positive electrode active material is discharged, silver is generated from the silver oxide of the positive electrode, but when this battery is charged, silver oxide crystals are generated around the silver, which substantially reduces the reaction area of the positive electrode active material and inhibits the subsequent battery reaction. However, when these compounds are dissolved in the alkaline electrolyte, ions derived from these compounds (manganese ions, tin ions, indium ions) are adsorbed to the positive electrode, suppressing the crystal growth of silver oxide and making the formed silver oxide crystals fine. Therefore, the occurrence of the problem of silver oxide crystals generated during charging of the battery inhibiting the battery reaction is suppressed, and it becomes possible to further improve the charge and discharge cycle characteristics of the secondary battery, for example.
[0070] Examples of manganese compounds dissolved in the alkaline electrolyte include manganese chloride, manganese acetate, manganese sulfide, manganese sulfate, manganese hydroxide, etc. Examples of tin compounds dissolved in the alkaline electrolyte include tin chloride, tin acetate, tin sulfide, tin bromide, tin oxide, tin hydroxide, tin sulfate, etc. Examples of indium compounds dissolved in the alkaline electrolyte include indium hydroxide, indium oxide, indium sulfate, indium sulfide, indium nitrate, indium bromide, indium chloride, etc.
[0071] From the viewpoint of better ensuring the above-mentioned effects, the concentrations of the indium compound, manganese compound and tin compound in the alkaline electrolyte (when only one of them is dissolved, it is the concentration thereof, and when two or more are dissolved, it is the total concentration thereof) are preferably 50 ppm or more, and more preferably 500 ppm or more, by mass, and are preferably 10,000 ppm or less, and more preferably 5,000 ppm or less.
[0072] In an alkaline battery, a separator is interposed between the positive and negative electrodes. Examples of separators that can be used in alkaline batteries include nonwoven fabrics mainly made of vinylon and rayon, vinylon-rayon nonwoven fabrics (vinylon-rayon mixed paper), polyamide nonwoven fabrics, polyolefin-rayon nonwoven fabrics, vinylon paper, vinylon-linter pulp paper, and vinylon-mercerized pulp paper. Alternatively, a separator may be made by stacking a hydrophilically treated microporous polyolefin film (such as a microporous polyethylene film or a microporous polypropylene film), a cellophane film, and a liquid-absorbing layer (electrolyte retention layer) such as a vinylon-rayon mixed paper. The thickness of the separator is preferably 20 to 500 μm.
[0073] In addition, when the alkaline battery is a secondary battery, it is preferable to dispose an anion conductive membrane between the positive electrode and the negative electrode, the anion conductive membrane being made of a polymer matrix and having particles of at least one metal compound selected from the group consisting of metal oxides, hydroxides, carbonates, sulfates, phosphates, borates, and silicates dispersed in the matrix. The anion conductive membrane also functions as a separator.
[0074] When the separator contains tellurium or a compound thereof, the content is adjusted to 0.4 parts by mass or more, more preferably 1 part by mass or more, and particularly preferably 2 parts by mass or more, per 100 parts by mass of the total amount of silver (Ag) element in the silver oxide, which is the positive electrode active material, from the viewpoint of better ensuring the above-mentioned effects by its use. However, if the amount of the additive in the separator is too large, there is a risk of inhibiting the permeation of ions in the electrolyte, which may result in a decrease in the load characteristics of the battery. Therefore, the content of the additive in the separator is adjusted to 10 parts by mass or less, more preferably 5 parts by mass or less, and particularly preferably 4 parts by mass or less, per 100 parts by mass of the total amount of silver (Ag) element in the silver oxide.
[0075] Furthermore, it is preferable that at least one of the negative electrode, the alkaline electrolyte, and the separator of the alkaline battery contains polyalkylene glycols or calcium compounds. In this case, the action of the polyalkylene glycols or calcium compounds can suppress the growth of zinc dendrites at the negative electrode, thereby further improving the charge / discharge cycle characteristics (in the case of a secondary battery) and storage characteristics of the alkaline battery.
[0076] The polyalkylene glycols are compounds having a structure in which alkylene glycols such as ethylene glycol, propylene glycol, and butylene glycol are polymerized or copolymerized, and may have a crosslinked or branched structure or a structure in which the terminals are substituted, and preferably have a weight-average molecular weight of about 200 or more. There is no particular upper limit to the weight-average molecular weight, but in order to more easily exert the effect of the addition, it is preferable that the compound is water-soluble, and usually, those having a molecular weight of 20,000 or less are preferably used, and those having a molecular weight of 5,000 or less are more preferably used.
[0077] More specifically, polyethylene glycols having a structure obtained by polymerizing ethylene glycol (polyethylene glycol, polyethylene oxide, etc.) and polypropylene glycols having a structure obtained by polymerizing propylene glycol (polypropylene glycol, polypropylene oxide, etc.) are preferably used, and copolymer compounds containing an ethylene oxide unit and a propylene oxide unit (polyoxyethylene polyoxypropylene glycol, etc.) may also be used.
[0078] When polyalkylene glycols are used, the amount thereof is preferably 0.01 to 1.5 parts by mass in terms of the amount of the polyalkylene glycols per 100 parts by mass of zinc particles.
[0079] The calcium compounds include calcium hydroxide, calcium oxide, calcium chloride, calcium sulfate, and other calcium compounds that are generated during discharge, such as Zn(OH)4 2-Examples of the compound include a compound that reacts with the above to produce a complex compound such as CaZn(OH)4, and the complex compound itself. Of these, calcium hydroxide and calcium oxide can be preferably used.
[0080] When a calcium compound is used, the amount of the calcium compound is preferably 5 to 40 parts by mass relative to 100 parts by mass of zinc particles.
[0081] In addition, when multiple components of the power generating element contain tellurium or a compound thereof, the total content of elemental tellurium held by each component of the power generating element should be within the above-mentioned range. When components other than the power generating element, such as an electrolyte absorber described below, are contained in the battery together with the power generating element, the total content of elemental tellurium held by the contents in the battery, including the power generating element, should be within the above-mentioned range.
[0082] FIG. 1 shows a vertical cross-sectional view that shows a schematic example of an alkaline battery of the present invention. The alkaline battery 1 shown in FIG. 1 is an example in which the present invention is applied to a flat battery, and a sealing plate 3 containing a negative electrode 5 is fitted into the opening of an outer can 2 containing a positive electrode 4 and a separator 6 via a ring-shaped gasket 7 with an L-shaped cross section, and the open end of the outer can 2 is tightened inward, and the gasket 7 abuts against the sealing plate 3, sealing the opening of the outer can 2 and forming a sealed structure inside the battery. That is, in the alkaline battery 1 shown in FIG. 1, power generating elements including a positive electrode 4, a negative electrode 5, and a separator 6 are loaded into the space (sealed space) in the battery container consisting of the outer can 2, the sealing plate 3, and the gasket 7, and further an alkaline electrolyte (not shown) is contained. The outer can 2 also serves as a positive electrode terminal, and the sealing plate 3 also serves as a negative electrode terminal.
[0083] Furthermore, in the alkaline battery 1 shown in FIG. 1, the peripheral edge of the positive electrode 4 is disposed between the inner bottom surface of the exterior can 2 and the bottom surface of the gasket 7.
[0084] Moreover, Fig. 2 shows a vertical cross-sectional view that typically illustrates another example of an alkaline battery of the present invention. The alkaline battery 1 shown in Fig. 2 is an example in which a porous electrolyte absorber 8 is disposed between the positive electrode 4 and the inner bottom surface of the outer can 2. As shown in Fig. 2, in the case of a flat alkaline battery having an outer can and a sealed can, a porous electrolyte absorber can be inserted between the positive electrode and the inner bottom surface of the outer can in order to prevent leakage of the electrolyte during assembly when the amount of electrolyte becomes large.
[0085] That is, even if the electrolyte is injected into the outer can, it takes a certain amount of time for the separator and the positive electrode to absorb the electrolyte, so that if the amount of electrolyte is large, the electrolyte is likely to leak when the can is sealed. However, if an electrolyte absorber is placed in advance on the inner bottom surface of the outer can before the positive electrode is placed in the outer can during assembly of the battery, the electrolyte absorber will absorb and retain a certain amount of electrolyte when the electrolyte is injected into the outer can, thereby suppressing leakage of the electrolyte.
[0086] The electrolyte absorber may be any porous sheet, and examples thereof include resin (including paper) porous sheets such as nonwoven fabric mainly made of vinylon and rayon, vinylon-rayon nonwoven fabric (vinylon-rayon mixed paper), polyamide nonwoven fabric, polyolefin-rayon nonwoven fabric, vinylon paper, vinylon-linter pulp paper, and vinylon-mercerized pulp paper; and porous carbon sheets made of fibrous carbon (carbon paper, carbon cloth, carbon felt, etc.).
[0087] The electrolyte absorber has a porosity of preferably 40% or more, more preferably 60% or more, since the electrolyte absorber has a better function of absorbing and retaining the electrolyte. However, if the electrolyte absorber has a porosity that is too large, the electrolyte retention function may be reduced, so the porosity is preferably 90% or less, more preferably 80% or less.
[0088] In addition, the average pore size of the electrolyte absorber is preferably 5 μm or more, more preferably 20 μm or more, from the viewpoint of quickly absorbing the electrolyte. However, if the pore size of the electrolyte absorber is too large, the electrolyte retention function may be reduced, so the average pore size is preferably 100 μm or less, more preferably 50 μm or less. The average pore size of the electrolyte absorber in this specification is a value measured based on the bubble point method specified in JIS K 3832.
[0089] Furthermore, the thickness of the electrolyte absorber is preferably 30 μm or more, more preferably 50 μm or more, from the viewpoint of being able to retain a relatively large amount of electrolyte. However, if the electrolyte absorber is too thick, it may be necessary to reduce the amount of positive and negative electrodes in the battery, which may cause a decrease in capacity, so the thickness is preferably 150 μm or less, more preferably 100 μm or less.
[0090] In addition, in a flat battery, when a conductive material such as a carbon sheet is used as the electrolyte absorber, the positive electrode and the outer can are electrically connected via the electrolyte absorber, so the use of the electrolyte absorber does not impair the current collection of the positive electrode. However, when an insulating electrolyte absorber such as a resin sheet is used, the contact area between the positive electrode and the inner bottom surface of the outer can becomes small, and there is a risk that the current collection of the positive electrode will be insufficient. Therefore, in a flat battery, it is preferable that the positive electrode and the side wall of the outer can are electrically connected. This makes it possible to improve the current collection of the positive electrode even if an insulating electrolyte absorber is used.
[0091] Conduction between the positive electrode and the side wall of the outer can may be achieved, for example, as shown in FIG. 2, by directly contacting the side surface of the positive electrode with the side wall of the outer can, or may be achieved, for example, by holding the positive electrode with a metal base and contacting this base with the side wall of the outer can.
[0092] The alkaline battery of the present invention is not limited to the flat type shown in FIG. 1 , but may also be of a cylindrical shape (cylindrical or square (rectangular tubular)) having a battery case in which a bottomed cylindrical outer can and a sealing plate are crimped and sealed via a gasket, or the outer can and a sealing plate are sealed by welding.
[0093] The exterior can of an alkaline battery can be made of, for example, nickel-plated iron or stainless steel.
[0094] In addition, as the sealing plate of an alkaline battery, for example, nickel-plated iron or stainless steel can be used. When zinc particles, which are the negative electrode active material, are in direct contact with the inner surface of the sealing plate, it is preferable to form a metal layer made of copper or a copper alloy such as brass on the surface of the sealing plate that is in contact with the negative electrode, and it is more preferable to further form a tin layer on the surface of the metal layer. The reason for forming a metal layer made of copper or a copper alloy on the surface of the sealing plate that is in contact with the negative electrode is to suppress the formation of a local battery with zinc and prevent the corrosion of zinc, but by further forming a tin layer on the surface of the metal layer, the corrosion prevention effect can be further enhanced.
[0095] Examples of gaskets for alkaline batteries include those made of nylon, polypropylene, and the like.
[0096] In the case of a flat alkaline battery, the shape in plan view may be circular or polygonal such as a quadrangle (square or rectangle), and in the case of a polygonal shape, the corners may be curved. EXAMPLES
[0097] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.
[0098] Example 1 Silver oxide (I) (AgO) containing 3.7% (by mass) of Bi relative to the total amount of silver with an average particle diameter of 1.4 μm: 88 parts by mass, and graphite particles (BET specific surface area: 20 m 2 / g, average particle size: 3.7 μm): 3.8 parts by mass, and carbon black (BET specific surface area: 68 m 2 A positive electrode mixture was prepared by mixing 1.2 parts by mass of acetylene black (average particle diameter: 35 nm, primary particles of which had a molecular weight of 1.01 g / g), 1 part by mass of TiO particles (average particle diameter: 250 nm), 3 parts by mass of tellurium dioxide, and 3 parts by mass of polytetrafluoroethylene (PTFE).
[0099] This positive electrode mixture: 73 mg was filled into a mold, and the filling density was 5.7 g / cm 3 A positive electrode mixture compact was produced by pressing the positive electrode mixture into a disk shape with a diameter of 5.2 mm and a height of 0.6 mm. In the positive electrode mixture constituting the positive electrode mixture compact, the amount of tellurium element per 100 parts by mass of Ag in silver (I) was 3.0 parts by mass. In addition, the positive electrode mixture did not contain cadmium, and a positive electrode substantially free of cadmium was obtained, which was made of the positive electrode mixture compact.
[0100] For the negative electrode active material, mercury-free zinc alloy particles, which contain 500 ppm In, 400 ppm Bi, and 10 ppm Al as additive elements and are commonly used in alkaline primary batteries, were used. The particle size of the zinc alloy particles determined by the above-mentioned method is the average particle diameter (D 50 ) was 120 μm, and the proportion of particles with a particle size of 75 μm or less was 25 mass % or less.
[0101] The zinc alloy particles and ZnO were mixed in a ratio (mass ratio) of 97:3 to obtain a composition for forming a negative electrode (negative electrode composition). 18 mg of this composition was weighed out and used to prepare a negative electrode.
[0102] The alkaline electrolyte used was an aqueous solution in which potassium hydroxide was dissolved at a concentration of 35% by mass, and zinc oxide was further dissolved at a concentration of 3% by mass.
[0103] 5 g of an aqueous dispersion of PTFE (solid content: 60% by mass), 2.5 g of an aqueous solution of sodium polyacrylate (concentration: 2% by mass), and 2.5 g of hydrotalcite particles (average particle size: 0.4 μm) were kneaded and rolled to produce a membrane with a thickness of 100 μm, which was then punched out into a circle with a diameter of 5.6 mm to produce an anion conductive membrane.
[0104] A multilayer film in which two graft films (thickness: 30 μm) composed of a graft copolymer having a structure in which acrylic acid is graft-copolymerized onto a polyethylene main chain were placed on either side of a cellophane film (thickness: 20 μm) was laminated with vinylon-rayon mixed paper (thickness: 100 μm), punched out into a circle with a diameter of 5.6 mm, and further layered with the anion conductive membrane to form a separator.
[0105] The positive electrode (positive electrode mixture molded body), negative electrode (negative electrode composition), alkaline electrolyte, and separator were sealed in a battery container consisting of an outer can made of a steel plate with gold plating on the inner surface, a sealing plate made of a copper-stainless steel (SUS304)-nickel clad plate, and an annular gasket made of nylon 66, to produce an alkaline secondary battery having a structure shown in FIG. 1 and a diameter of 5.8 mm and a thickness of 2.7 mm. Note that a part of the alkaline electrolyte was dropped into the outer can before the positive electrode was housed in the outer can, and the remainder was mixed with the negative electrode composition in advance to assemble the battery. The separator was also arranged so that the anion conductive membrane faced the negative electrode.
[0106] Example 2 An alkaline secondary battery was produced in the same manner as in Example 1, except that a positive electrode mixture was prepared by mixing 90.5 parts by mass of the silver oxide (I) (Ag2O), 3.8 parts by mass of graphite particles, 1.2 parts by mass of carbon black, 1 part by mass of TiO2 particles, 0.5 parts by mass of tellurium dioxide, and 3 parts by mass of polytetrafluoroethylene (PTFE). In the positive electrode mixture constituting the positive electrode mixture molded body, the amount of tellurium element per 100 parts by mass of Ag in the silver oxide (I) was 0.5 parts by mass.
[0107] Example 3 An alkaline secondary battery was produced in the same manner as in Example 1, except that a positive electrode mixture was prepared by mixing 89.5 parts by mass of the silver oxide (I) (Ag2O), 3.8 parts by mass of graphite particles, 1.2 parts by mass of carbon black, 1 part by mass of TiO2 particles, 1.5 parts by mass of tellurium dioxide, and 3 parts by mass of polytetrafluoroethylene (PTFE). In the positive electrode mixture constituting the positive electrode mixture molded body, the amount of tellurium element per 100 parts by mass of Ag in the silver oxide (I) was 1.5 parts by mass.
[0108] Comparative Example 1 An alkaline secondary battery was produced in the same manner as in Example 1, except that a positive electrode mixture was prepared by mixing 91 parts by mass of silver oxide (I) (AgO), 3.8 parts by mass of graphite particles, 1.2 parts by mass of carbon black, 1 part by mass of TiO particles, and 3 parts by mass of polytetrafluoroethylene (PTFE).
[0109] [Measurement of the internal resistance of a battery] Five batteries each of Examples 1 to 3 and Comparative Example 1 were prepared, and the internal resistance at 20° C. was measured at a frequency of 1 kHz by an AC impedance method, and the average value was calculated as the internal resistance of the battery.
[0110] [Charge / discharge cycle characteristic evaluation] Five batteries each of Examples 1 to 3 and Comparative Example 1 were prepared, and a charge / discharge cycle was repeated in which a constant current discharge was performed at a current value of 2.1 mA until the voltage reached 1.2 V, followed by a constant current / constant voltage charge at a constant current of 2.1 mA until the voltage reached 1.8 V, and then a constant voltage charge was performed at a constant voltage of 1.8 V until the current reached 0.21 mA. The discharge capacity of each battery per cycle was calculated as the average value of the five batteries, and the charge / discharge cycle characteristics were evaluated from the ratio of the discharge capacity at the 100th cycle to the discharge capacity at the 10th cycle (capacity retention rate).
[0111] The results are shown in Table 1.
[0112] [Table 1]
[0113] As shown in Table 1, the alkaline secondary batteries of Examples 1 to 3 having a positive electrode containing silver oxide (I) and tellurium dioxide (a tellurium compound) had lower internal resistance and higher capacity retention rates during evaluation of the charge-discharge cycle characteristics, and thus had superior charge-discharge cycle characteristics, compared to the battery of Comparative Example 1 having a positive electrode that did not contain a tellurium compound.
[0114] Example 4 Silver oxide (I) (AgO) containing 3.7% (by mass) of Bi relative to the total amount of silver with an average particle diameter of 1.4 μm: 90.3 parts by mass, and graphite particles (BET specific surface area: 20 m 2 / g, average particle size: 3.7 μm): 3.8 parts by mass, and carbon black (BET specific surface area: 68 m 2 A positive electrode mixture substantially free of cadmium was prepared by mixing 1.9 parts by mass of acetylene black (average particle size: 35 nm, primary particles of which were 1.0 parts by mass / g), 1 part by mass of TiO2 particles (average particle size: 250 nm), and 3 parts by mass of polytetrafluoroethylene (PTFE). A positive electrode made of a positive electrode mixture compact was produced in the same manner as in Example 1, except that this positive electrode mixture was used.
[0115] As an alkaline electrolyte, a mixed solution was prepared by dissolving potassium hydroxide at a concentration of 35% by mass, zinc oxide at a concentration of 3% by mass, and further dissolving lithium hydroxide: 1% by mass, polyethylene glycol: 1% by mass, and tellurium dioxide: 9.2% by mass. The content of elemental tellurium in the electrolyte was 7.4% by mass.
[0116] Except for using the above-mentioned positive electrode (positive electrode mixture molded body) and alkaline electrolyte, an alkaline secondary battery was produced in the same manner as in Example 1. The total content of elemental tellurium in the power generating element of this alkaline secondary battery was 3.1 parts by mass with respect to 100 parts by mass of the total amount of elemental silver in the positive electrode active material.
[0117] Example 5 An alkaline electrolyte was prepared in the same manner as in Example 4, except that potassium hydroxide was changed to sodium hydroxide, and an alkaline secondary battery was fabricated in the same manner as in Example 4, except that the alkaline electrolyte was used.
[0118] Comparative Example 2 An alkaline secondary battery was prepared in the same manner as in Example 4, except that a mixed solution (aqueous solution not containing tellurium) was used in which potassium hydroxide was dissolved in an alkaline electrolyte at a concentration of 35% by mass, zinc oxide was dissolved in an aqueous solution at a concentration of 3% by mass, and lithium hydroxide: 1% by mass and polyethylene glycol: 1% by mass were further dissolved in the aqueous solution.
[0119] Comparative Example 3 An alkaline electrolyte was prepared in the same manner as in Comparative Example 2 except that potassium hydroxide was changed to sodium hydroxide, and an alkaline secondary battery was fabricated in the same manner as in Comparative Example 1 except that the alkaline electrolyte was used.
[0120] Example 6 Except for containing 87.3 parts by mass of silver oxide (I) and 3 parts by mass of tellurium dioxide instead of 90.3 parts by mass of silver oxide (I), a positive electrode mixture was prepared in the same manner as in Example 4. Furthermore, an alkaline secondary battery was fabricated in the same manner as in Comparative Example 2 except for using the positive electrode mixture.
[0121] In the positive electrode mixture, the amount of elemental tellurium per 100 parts by mass of Ag in the silver (I) oxide was 3.1 parts by mass.
[0122] Example 7 An alkaline secondary battery was produced in the same manner as in Example 6, except that the same alkaline electrolyte as in Comparative Example 3 was used.
[0123] Five batteries for each of Examples 4 to 7 and Comparative Examples 2 and 3 were prepared, and the internal resistance of the batteries was determined in the same manner as for the battery of Example 1.
[0124] Five batteries each of Examples 4 to 7 and Comparative Examples 2 and 3 were prepared, and charge / discharge cycles were repeated under the same conditions as for the battery of Example 1. The discharge capacity of each battery at the 150th cycle was measured, and the charge / discharge cycle characteristics were evaluated from the average value.
[0125] The results are shown in Table 2.
[0126] [Table 2]
[0127] The alkaline secondary batteries of Examples 4 to 7 maintained a high discharge capacity even after 150 cycles and had excellent charge-discharge cycle characteristics, compared to the batteries of Comparative Examples 2 and 3 having alkaline electrolytes not containing tellurium compounds.
[0128] In addition, in the alkaline secondary batteries of Examples 6 and 7, tellurium dioxide was contained in the positive electrode, which allowed the additive to act efficiently within the positive electrode, thereby reducing the internal resistance of the battery compared to the batteries of Comparative Examples 2 and 3, respectively.
[0129] Example 8 As the alkaline electrolyte to be contained in the battery container, 25.8 mg of the alkaline electrolyte prepared in Example 4 was used. A circular electrolyte absorber (porosity: 65%, average pore size: 20 μm, thickness: 100 μm) made of vinylon-rayon nonwoven fabric with a diameter of 5.5 mm was placed on the inner bottom surface of an outer can made of a steel plate with an inner surface plated with gold, and 9 μL of the alkaline electrolyte was dropped on it, and then the positive electrode (positive electrode mixture molded body) similarly prepared in Example 4 was placed in the outer can. The remaining alkaline electrolyte was mixed with the negative electrode composition in advance, and was placed together with the negative electrode composition in a sealing plate made of a copper-stainless steel (SUS304)-nickel clad plate fitted with a ring-shaped gasket made of nylon 66. Thereafter, an alkaline secondary battery having a structure similar to that shown in FIG. 2, a diameter of 5.8 mm, and a thickness of 2.7 mm was assembled in the same manner as in Example 1.
[0130] Example 9 An alkaline secondary battery was produced in the same manner as in Example 8, except that no electrolyte absorber was used.
[0131] The alkaline secondary batteries of Examples 8 and 9 were subjected to the following evaluations.
[0132] <Evaluation of leakage during manufacturing> When 20 alkaline secondary batteries each of Example 8 and Example 9 were assembled, the number of batteries that had leaked was counted.
[0133] <Discharge characteristic evaluation> The discharge capacity of the batteries of Example 8 and Example 9 was measured by discharging at a current value of 1.0 mA until the voltage reached 1.0 V. The battery of Example 9 used was one that did not leak during assembly.
[0134] The results of each of the above evaluations are shown in Table 3.
[0135] [Table 3]
[0136] As shown in Table 3, in the alkaline secondary battery of Example 9, which did not have an electrolyte absorber, some of the batteries leaked during assembly, but in the flat alkaline secondary battery of Example 8, due to the action of the electrolyte absorber, no leakage was observed during assembly and the battery had good productivity.
[0137] In addition, the battery of Example 8 used an electrolyte absorber made of an insulating material, but by establishing electrical continuity between the positive electrode and the side wall of the outer can, it was possible to ensure a discharge capacity equivalent to that of the battery of Example 9, which did not have an electrolyte absorber.
[0138] The present invention can be implemented in other forms than those described above without departing from the spirit of the present invention. The embodiments disclosed in this application are merely examples, and the present invention is not limited to these embodiments. The scope of the present invention shall be interpreted in accordance with the description of the appended claims rather than the description of the above specification, and all modifications within the scope of the claims are included in the scope of the claims. [Industrial Applicability]
[0139] The alkaline battery of the present invention can be used in the same applications as conventionally known alkaline batteries (primary batteries or secondary batteries). [Explanation of symbols]
[0140] 1 alkaline battery 2 Outer can 3 Sealing plate 4 Positive electrode 5 Negative electrode 6 Separator 7 Gasket 8 Electrolyte absorber
Claims
1. A positive electrode for an alkaline battery, comprising a molded body formed of a positive electrode mixture containing silver oxide as a positive electrode active material, or a positive electrode mixture layer formed of the positive electrode mixture, The positive electrode mixture is a mixture of the positive electrode active material and tellurium or a compound thereof, the content of elemental tellurium in the positive electrode mixture is 0.4 parts by mass or more relative to 100 parts by mass of the total amount of elemental silver in the positive electrode active material, A positive electrode for an alkaline battery, which is substantially free of cadmium.
2. 2. The positive electrode for an alkaline battery according to claim 1, wherein the content of elemental tellurium in the positive electrode mixture is 10 parts by mass or less, based on 100 parts by mass of the total amount of elemental silver in the positive electrode active material.
3. The positive electrode active material contains silver oxide (I), 2. The positive electrode for an alkaline battery according to claim 1, wherein the proportion of the silver (I) oxide in the total amount of the silver oxide in the positive electrode mixture is 60 mass % or more.
4. 2. The positive electrode for an alkaline battery according to claim 1, wherein the tellurium compound is an oxide of tellurium.
5. An alkaline battery having a positive electrode containing silver oxide as a positive electrode active material, a negative electrode, a separator, and an alkaline electrolyte as power generating elements, An alkaline battery comprising the alkaline battery positive electrode according to any one of claims 1 to 4 as the positive electrode.
6. An alkaline battery having a positive electrode containing silver oxide as a positive electrode active material, a negative electrode, a separator, and an alkaline electrolyte as power generating elements, At least one of the negative electrode, the separator, and the alkaline electrolyte contains tellurium or a compound thereof; the total content of elemental tellurium contained in the contents of the battery is 0.4 parts by mass or more relative to 100 parts by mass of the total amount of elemental silver in the positive electrode active material; 13. An alkaline battery, wherein the positive electrode is substantially free of cadmium.
7. 7. The alkaline battery according to claim 6, wherein the total content of elemental tellurium contained in the contents of the battery is 10 parts by mass or less, based on 100 parts by mass of the total amount of elemental silver in the positive electrode active material.
8. The positive electrode active material contains silver oxide (I), 7. The alkaline battery according to claim 6, wherein the proportion of the silver (I) oxide in the total amount of the silver oxide in the positive electrode mixture is 60 mass % or more.
9. 7. The alkaline battery according to claim 6, wherein the tellurium compound comprises an oxide of tellurium.
10. A method for producing an alkaline battery according to claim 5, comprising the steps of: A method for producing an alkaline battery, comprising using the positive electrode for an alkaline battery according to claim 1 as the positive electrode.
11. A method for producing an alkaline battery according to claim 6, comprising the steps of:
2. The method for producing an alkaline battery, wherein the alkaline electrolyte is an alkaline electrolyte in which tellurium or a compound thereof is dissolved.
12. The method for producing an alkaline battery according to claim 11, wherein the content of elemental tellurium in the alkaline electrolyte is 0.1 to 10 mass %.
Citation Information
Patent Citations
JP1975157837A
Preparation of silver peroxide
JP1982011823A